Studi Literatur Review : Geogebra Sebagai Media Belajar Untuk Mengetahui Kemampuan Komputasi Peserta Didik - Sri Rahayu Ningsi; Yahfizham (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Geogebra is a computer software that is useful for visualizing objects in mathematics effectively and efficiently. This research aims to look at Geogebra as a learning medium to determine students' computing abilities. This research takes the type of literature study research by identifying and evaluating the results of previous research. In this research, 3 previous journals were identified. From the results of this research, it can be seen that Geogebra can improve students' computational thinking abilities